KEARIFAN LOKAL MASYARAKAT DALAM MELINDUNGI RIMBO LARANGAN TERATAK AIR HITAM DI DESA SEBERANG TERATAK AIR HITAM KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Aprian, Aprian; Yoza, Defri; Mukhamadun, Mukhamadun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The local wisdom is needed in the management of forest protection. Knowledge in the form of customs rules, culture, and activities in forest management will preserve Rimbo Larangan Taratak Air Hitam. This research aims are to determine the form andÂ factorÂ the resistence of local wisdom in Rimbo Larangan Teratak Air Hitam. The method use is descriptive qualitative. Data collection is done with the interview or debriefing with the respondent. The sampling technique used in this research isÂ the Purposive Sampling. The questions asked are open-ended with the intention to provide the opportunity for respondents to express their opinion. The interview process was documented in the form of written notes, photographs, and recordings. The research conducted in the village of Seberang Taratak Air Hitam Sentajo Raya subdistrict Kuantan Singingi District. The results of this research is the local wisdom in Rimbo Larangan Taratak Air Hitam shaped custom rules, such as an appeal to maintain forests and a ban on activities which would damage the forest. There are 3 mains factors in maintaining local wisdom that their traditional institutions, public awareness, and the attention from the Kuantan Singingi Forestry Departement.Keywords: Local Wisdom, RimboLarangan, The Village Teratak Air Hitam, District KuantanSingingi